Comparative clinical efficacy of single-incision thoracoscopic bullectomy combined with C-shaped electrocautery pleurodesis vs. chemical pleurodesis in the management of spontaneous pneumothorax - Zhong, Bin; Wu, Qiyong; Zhang, Ming (Frontiers in Surgery, 2024)
ObjectiveThis study aims to observe the clinical efficacy of single-incision thoracoscopic bullectomy combined with C-shaped electrocautery pleurodesis compared to traditional iodine chemical pleurodesis in the treatment of patients with spontaneous pneumothorax.MethodsA total of 128 patients with spontaneous pneumothorax who underwent surgical treatment at our institution from January 2021 to December 2022 were selected. Patients were categorized into the study group (n = 65) and the control group (n = 63) based on the surgical method used. The study group received C-shaped pleura cautery for pleurodesis, while the control group underwent traditional iodine chemical pleurodesis. Surgical and clinical outcomes were evaluated, and recurrence rates within one year postoperatively were compared. Serum C-reactive protein (CRP) levels and visual analog scale (VAS) scores were measured at different time points.ResultsNo significant differences were observed between the two groups regarding surgical duration, intraoperative blood loss, or postoperative hospital stay (p > 0.05). However, the study group demonstrated significantly lower serum CRP levels and VAS scores on postoperative days 1 and 2, as well as reduced drainage volumes compared to the control group (p < 0.05). The recurrence rates of pneumothorax within one year postoperatively did not differ significantly between the groups (p > 0.05).ConclusionSingle-incision thoracoscopic bullectomy combined with C-shaped electrocautery pleurodesis is an effective treatment for spontaneous pneumothorax. Compared to traditional iodine chemical pleurodesis, this method causes less pleural irritation, results in lower postoperative pain and drainage, and facilitates patient recovery, making it a safe and reliable option for the management of spontaneous pneumothorax.